The Effect of Adding Mannitol to Lidocaine on the Anesthesia of Teeth with Inflamed Pulp in Cat - M Bidar; A Jalali; G Sahranavard (Journal of Kerman University of Medical Sciences, 2005)
Achieving complete anesthesia in the presence of inflammed pulp is one of the main problems in root canal therapy, and researchers are trying to find a more efficient anesthetic drug for these cases. The main goal of this study was to compare the analgesic effect of lidocaine and lidocaine mixed with mannitol in teeth with inflamed pulp. By using an electrophysiological method the anesthetic effect of lidocaine and lidocaine - mannitol injections on 24 mandibular canine teeth belonging to 12 cats were compared. At the first stage, right and left canines were exposed to the oral cavity for about 3 days in order to induce pulp inflammation. At the second stage, the inferior alveolar canal was exposed by a surgical flap and the extraction of the covering bone. Then recording electrodes were connected to the inferior alveolar nerve and stimulating electrodes were connected to the canines teeth. The teeth were stimulated by increasing the voltage with a stimulator. The lowest voltage that produced the highest amplitude of the neurologicalwave was considered as the main voltage of the study and neurograms were recorded before and after drug injections in each tooth. Lidocaine and lidocaine – mannitol were used alternatively for each side of the mandible. Mann Whitney test was used for data analysis. Based on the obtained results there is no significant difference between the two anesthetic agents in decreasing the amplitude of the neurological wave